Konsep Pendidikan Islam Holistik Dalam Memenangkan Persaingan di Era Milenial - Amie Primarni (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2019)
This study aims to produce an Educational Concept that is able to win competition in the Mileneal Era. Thisstudy uses a qualitative method with a literature study approach. This research approach uses analysis from theperspective of anthropology, sociology and educational psychology. Using triangulation techniques, the writer triesto construct the construct of a learning concept. In conclusion, the results of this study resulted in a concept of TheFoundation Of Learning Process, a foundation of continuous learning that gradually develops spiritual, intellectual,physical and emotional development abilities, in a planned, structured manner.